A Rethinking of Prosperity Teaching in the New Pentecostal Churches in Nigeria - Ayegboyin, Deji I. (Black Theology, 2006)
This article, which is based on a research study in Nigeria, evaluates prosperity theology, which has gained much currency all over Africa. The article takes issue with the doctrine because it raises some crucial and somewhat awkward questions for all concerned. The teaching lacks a consensus definition; it is weakly theorized, could be unscriptural and seems oblivious to some significant features in the early church as illustrated in the Acts of the Apostles. The final goal of the article is to suggest a reconstruction of prosperity theology, which will evolve one that is unquestionably scriptural and contextual.
free